Investigation of Binding Efficacy of Pectin Isolated from Solanum betaceum Cav using Tabletting Technology - Benedict Jose C (Journal of Global Pharma Technology, 2020)
Pectin’s are widely used in food industry and Pharmaceutical industry. It is also a natural part of the human diet. The current research work deals with the isolation and preliminary characterization of pectin from tree tomato (Solanum betaceaum Cav) and further to evaluate its binding property with starch and Poly Vinyl Pyrollidone (PVP). The pectin was subjected to phytochemical and physicochemical characterization and its suitability to use as binding agent. FT-IR spectroscopy, DSC studies were performed for drug, Solanum betaceaum Cav pectin (SBP) powder and the tablets were prepared with isolated pectin and other binders. Paracetamol tablets were prepared by wet granulation method containing mannitol and microcrystalline cellulose as diluents, using 4%, 8% and 12 %w/w of SBP, starch and PVP as binding agents in the tablet formulation. Precompressional properties of granules and tablets such as Carr’s index, Hausner’s ratio and angle of repose and quality control tests like weight variation, thickness, friability, hardness and disintegration time were determine and found satisfactory. The in vitro release studies shows that release rate of drug is decreased with increase in the SBP percentage in the formulation. Solanum betaceaum Cav pectin powder showed good binding. The binding efficiency of Solanum betaceaum Cav pectin was comparable with binding character of starch 12% and PVP 8%. The pectin isolated from Solanum betaceaum Cav can be used as binder in the formulation of tablets. Keywords: Solanum betaceaum Cav pectin, Fruit pectin, Tree tomato, Tamarillo pectin, Natural binder, Natural excipients.